New agricultural investment models and agrarian change in South Africa - (:unkn) unknown (My University, 2012)
The end of the South African commercial farmer is often proclaimed, mainly as a result of land reform and the lack of encouraging agricultural policy measures. This paper draws attention to a similar tendency, not related to South Africa's positive actions, however, but to a profound agrarian restructuring related to new agricultural investment models. These models, promoted by macro-actors such as banking corporations, investment funds, asset management companies and agricultural engineering companies, often foreign to the agricultural sector, integrate the primary agricultural production within well-connected, totally integrated, finance-value-chains. In these models, macro-actors oversee, control and own the entire process (supply of inputs, monitoring of the harvest, hedge and sale of the production) whereas independent farmers become 'service-providers' of these institutions, as they do not possess their harvest, nor do they engage in decision-making and in several cases do not even own the land. The paper describes and analyses the different agricultural production models being developed in the South African context and discusses their application and implications for the country's agricultural development trajectories. As such, it poses significant questions regarding the "financiarisation and corporisation" of the agricultural sector, the concentration process on-going in the sector, the regulation of the sector by often foreign controlled non-agricultural entities and, probably most importantly, the status of the independent farmer in South Africa.
Keywords: African Research